The Effects of Dietary Silybin Supplementation on the Growth Performance and Regulation of Intestinal Oxidative Injury and Microflora Dysbiosis in Weaned Piglets - Long Cai; Ge Gao; Chenggang Yin; Rong Bai; Yanpin Li; Wenjuan Sun; Yu Pi; Xianren Jiang; Xilong Li (Antioxidants, 2023)
Oxidative stress is the major incentive for intestinal dysfunction in weaned piglets, which usually leads to growth retardation or even death. Silybin has caught extensive attention due to its antioxidant properties. Herein, we investigated the effect of dietary silybin supplementation on growth performance and determined its protective effect on paraquat (PQ)-induced intestinal oxidative damage and microflora dysbiosis in weaned piglets. In trial 1, a total of one hundred twenty healthy weaned piglets were randomly assigned into five treatments with six replicate pens per treatment and four piglets per pen, where they were fed basal diets supplemented with silybin at 0, 50, 100, 200, or 400 mg/kg for 42 days. In trial 2, a total of 24 piglets were randomly allocated to two dietary treatments with 12 replicates per treatment and 1 piglet per pen: a basal diet or adding 400 mg/kg silybin to a basal diet. One-half piglets in each treatment were given an intraperitoneal injection of paraquat (4 mg/kg of body weight) or sterile saline on day 18. All piglets were euthanized on day 21 for sample collection. The results showed that dietary supplementation with 400 mg/kg silybin resulted in a lower feed conversion ratio, diarrhea incidence, and greater antioxidant capacity in weaned piglets. Dietary silybin enhanced intestinal antioxidant capacity and mitochondrial function in oxidative stress piglets induced by PQ. Silybin inhibited mitochondria-associated endogenous apoptotic procedures and then improved the intestinal barrier function and morphology of PQ-challenged piglets. Moreover, silybin improved intestinal microbiota dysbiosis induced by the PQ challenge by enriching short-chain fatty-acid-producing bacteria, which augmented the production of acetate and propionate. Collectively, these findings indicated that dietary silybin supplementation linearly decreased feed conversion ratio and reduced diarrhea incidence in normal conditions, and effectively alleviated oxidative stress-induced mitochondrial dysfunction, intestinal damage, and microflora dysbiosis in weaned piglets.